Pemberdayaan Perempuan dengan Kegiatan Ecoprint di Dusun Pogalan Atas melalui Ecocreative of Sempurna - Anindya Khoirunnisa; Karunia Galih Permadani; Vira Syafira; Choirul Muniroh; Bagas Rezky (Jurnal Pemberdayaan Masyarakat, 2024)
Ecoprint is a technique for creating special designs on fabric using color pigments found in plant parts. This training was carried out as community service to provide skills to the residents of Kaponan Village, especially Pogalan Atas Hamlet, on how to make ecoprints. Pogalan Atas Hamlet was chosen as the location for ecoprint production because it has interesting potential for developing ecoprint production. The diversity of plant species in this hamlet offers a rich variety of colors and textures, which are key to creating attractive, high-quality ecoprint designs. The aim of this ecoprint training program is to help family welfare and generate additional income by encouraging the advancement of women's life skills in Pogalan Atas Hamlet. This training program was carried out in Pogalan Atas Hamlet, Kaponan Village, Pakis District, Magelang Regency using a direct practice method. A series of events were attended by children, mothers, youth organizations and women's communities in Upper Pogalan Hamlet. All training participants carefully practice ecoprinting and create ecoprint items, such as ecoprint tote bags. Apart from that, training participants are given training on how to attract potential customers and change ecoprint fabric results into products with higher selling value. In this training, the community gains improved life skills, thereby increasing their ability to better utilize existing local potential.